Estimating reaction kinetics of cementitious pastes containing fly ash. (September 2020) - Glosser, Deborah; Suraneni, Prannoy; Isgor, O. Burkan; Weiss, W. Jason
Abstract: This paper proposes an approach to estimate reaction kinetics for major fly ash glassy oxides in cementitious mixtures. The approach is compared to experimental results from multiple independent datasets. The kinetic model is based on the rate limiting step for various oxides and phases using the general form of a widely used model for ordinary portland cement (OPC)-based systems. The empirical parameters in the model were fit from dissolution studies for glass oxides in two fly ashes from literature using a nonlinear optimization algorithm. The outputs of the model provide the inputs needed to introduce reaction kinetics into thermodynamic simulations at non-equilibrium conditions. The model is used to determine the amount of each phase that can react by estimating the dissolved mass of each major cement phase and fly ash glass oxide at different ages. This approach enables accurate modeling predictions of solid hydration products (such as calcium hydroxide and ettringite), pore solution pH, and pore solution chemistry at any age for any OPC/fly ash system. Results from the model and thermodynamic calculations are compared to a modeling approach without kinetic constraints on the fly ash, assuming 100% reactivity. The prediction of reaction products made assuming 100% fly ash reactivity significantly differs from experimental values when a fly ash kinetic model is not used. Predictions are greatly improved when the model is used. The model can be used as a framework for future modeling efforts, and the empirical parameters be updated as additional dissolution studies and thermodynamic data become available.